DAMPening COVID-19 Severity by Attenuating Danger Signals - Silva-Lagos, Luis A.; Pillay, Janesh; van Meurs, Matijs; Smink, Alexandra; van der Voort, Peter H. J.; de Vos, Paul (Frontiers in Immunology, 2021)
COVID-19 might lead to multi-organ failure and, in some cases, to death. The COVID-19 severity is associated with a “cytokine storm.” Danger-associated molecular patterns (DAMPs) are proinflammatory molecules that can activate pattern recognition receptors, such as toll-like receptors (TLRs). DAMPs and TLRs have not received much attention in COVID-19 but can explain some of the gender-, weight- and age-dependent effects. In females and males, TLRs are differentially expressed, likely contributing to higher COVID-19 severity in males. DAMPs and cytokines associated with COVID-19 mortality are elevated in obese and elderly individuals, which might explain the higher risk for severer COVID-19 in these groups. Adenosine signaling inhibits the TLR/NF-κB pathway and, through this, decreases inflammation and DAMPs’ effects. As vaccines will not be effective in all susceptible individuals and as new vaccine-resistant SARS-CoV-2 mutants might develop, it remains mandatory to find means to dampen COVID-19 disease severity, especially in high-risk groups. We propose that the regulation of DAMPs via adenosine signaling enhancement might be an effective way to lower the severity of COVID-19 and prevent multiple organ failure in the absence of severe side effects.